RSSI-based Human Presence Detection System for Energy Saving Automation - Mohamed Habaebi; Rafhanah Rosli; Md Rafiqul Islam (IAES Indonesian Section, 2017)
WiFi facilitates computers and devices to connect with the Internet and each other using radio frequency signals that has Received Signal Strength Indicator or RSSI as its standard feature. With the use of RSSI value, a human presence detection technique to support energy saving by automating appliances is developed. It has attracted interest of researchers for its advantages like simplicity and low-cost. A system module that can detect the presence of human is achieved by designing and developing a device that utilizes off-the-shelves hardware, implementing a statistical analysis algorithm and by testing and evaluating the performance of the developed system in a real life environment. The result of the system module’s performance analysis in this research has shown 100% sensitivity, specificity and accuracy to the solution. The solution and approach can be used to support energy saving by automating appliances, resulting in a greener environment and a better financial efficiency.